Clinical implications of medulloblastoma subgroups: incidence of CSF diversion surgery - Christian Schneider; Vijay Ramaswamy; Abhaya V. Kulkarni; James T. Rutka; Marc Remke; Uri Tabori; Cynthia Hawkins; Éric Bouffet; Michael D. Taylor (2014)
While medulloblastoma was initially thought to comprise a single homogeneous entity, it is now accepted that it in fact comprises 4 discrete subgroups, each with its own distinct demographics, clinical presentation, transcriptomics, genetics, and outcome. Hydrocephalus is a common complication of medulloblastoma and not infrequently requires CSF diversion. The authors report the incidence of CSF diversion surgery in each of the subgroups of medulloblastoma (Wnt, Shh, Group 3, and Group 4).The medical and imaging records for patients who underwent surgery for medulloblastoma at The Hospital for Sick Children were retrospectively reviewed. The primary outcome was the requirement for CSF diversion surgery either before or within 60 days of tumor resection. The modified Canadian Preoperative Prediction Rule for Hydrocephalus (mCPPRH) was compared among subgroups.Of 143 medulloblastoma patients, treated from 1991 to 2013, sufficient data were available for 130 patients (15 with Wnt, 30 with Shh, 30 with Group 3, and 55 with Group 4 medulloblastomas). Of these, 28 patients (22%) ultimately underwent CSF diversion surgery: 0% with Wnt, 29% with Shh, 29% with Group 3, and 43% with Group 4 tumors. Patients in the Wnt subgroup had a lower incidence of CSF diversion than all other patients combined (p = 0.04). Wnt patients had a lower mCPPRH score (lower risk of CSF diversion, p = 0.045), were older, had smaller ventricles at diagnosis, and had no leptomeningeal metastases.The overall rate of CSF diversion surgery for Shh, Group 3, and Group 4 medulloblastomas is around 30%, but no patients in the present series with a Wnt medulloblastoma required shunting. The low incidence of hydrocephalus in patients with Wnt medulloblastoma likely reflects both host factors (age) and disease factors (lack of metastases). The absence of hydrocephalus in patients with Wnt medulloblastomas likely contributes to their excellent rate of survival and may also contribute to a higher quality of life than for patients in other subgroups.